The effect of passive deformation of dragonfly wing on aerodynamic characteristics - Hisayoshi NAKA; Hiromu HASHIMOTO (Nihon Kikai Gakkai ronbunshu, 2016)
Dragonflies can perform both of gliding and flapping flight and have high maneuverability in spite of small-size. The aim of this study is to develop Micro Air Vehicle (MAV) based on the flight of dragonfly. The characteristics of wings are very important for development of MAV. Dragonfly wing is easy to be passively deformed in the tip side from the nodus in flapping flight, and thereby, aerodynamic force is generated effectively. In this study, the effect of passive deformation of wing on aerodynamic force was investigated using fluid-structure interaction analysis to develop the artificial wing suitable for dragonfly-like MAV. In this study, aerodynamic characteristics of wings in the gliding flight and aerodynamic force generated in flapping flight are numerically analyzed. In this analysis, nodus wing models, which can deform passively, and rigid wing model, which cannot deform, are used. Nodus wing model imitates the nodus structure; the tip side of this model is free to rotate around leading edge. As a result of gliding flight, the lift coefficient of the nodus wing was lower in low-angle of attack and was higher in high-angle of attack, compared to rigid wing. Moreover, the more flexible wings are, the more change. The gliding flight is low-angle of attack usually. Therefore, flexible wing is less suitable for the gliding flight than inflexible wing. As a result of flapping flight, the nodus wing made drag force generated during down stroke lower compared with the rigid wing. However, thrust forces generated during up stroke in both wings were the same. Therefore, flexible wing is more suitable for the flapping flight than inflexible wing. The wings of dragonfly-like MAV need to appropriate level of flexibility to upgrade the performance in both case of gliding and flapping flight.